NK cells inhibit humoral immunity by reducing the abundance of CD4+ T follicular helper cells during a chronic virus infection. Issue 2 (18th May 2015) - Cook, Kevin D; Kline, Hannah C; Whitmire, Jason K
Abstract : Virus persistence is increased by NK cells that inhibit antiviral CD4 + TFH cells and early B cell responses. Abstract: There is a need to understand better how to improve B cell responses and immunity to persisting virus infections, which often cause debilitating illness or death. People with chronic virus infection show evidence of improved virus control when there is a strong neutralizing antibody response, and conversely, B cell dysfunction is associated with higher viral loads. We showed previously that NK cells inhibit CD4 + and CD8 + T cell responses to disseminating LCMV infection and that depletion of NK cells attenuates chronic infection. Here, we examined the effect of NK cell depletion on B cell responses to LCMV infection in mice. Whereas mice infected acutely generated a peak level of antibody soon after the infection was resolved, mice infected chronically showed a continued increase in antibody levels that exceeded those after acute infection. We found that early NK cell depletion rapidly increased virus-specific antibody levels to chronic infection, and this effect depended on CD4 + T cells and was associated with elevated numbers of CXCR5 + CD4 + TFH cells. However, the NK cell-depleted mice controlled the infection and by 1 mo pi, had lower TFH cell numbers and antibody levels compared with mice with sustained infection. Finally, we show that NK cell depletion improved antiviral CD8 + T cell responses only when B cells and virus-specific antibody were present. Our data indicate that NK cells diminish immunity to chronic infection, in part, by suppressing TFH cell and antibody responses.